THE IMPORTANCE OF STAKEHOLDER MANAGEMENT FOR THE SUCCESS OF CORPORATE SOCIAL RESPONSIBILITY (International Seven Journal of Multidisciplinary, 2025)
Stakeholder management and corporate social responsibility (CSR) are complementary practices that aim to align business objectives with societal expectations and sustainable development. Stakeholder management focuses on identifying and engaging interest groups, such as customers, employees, communities, and investors, who impact or are impacted by the company's operations, seeking to maintain a balanced and positive relationship. In contrast, CSR integrates social and environmental concerns into business operations, promoting a positive impact beyond profit. In this context, communication and transparency tools—such as sustainability reports and social media—are essential for informing stakeholders about the company’s practices and outcomes, reinforcing trust and highlighting the company’s ethical commitments to society and the environment. The objective of this research is to provide an overview of studies on stakeholder management, reviewing key models and theoretical propositions, as well as investigating the phenomena discussed in empirical articles on the topic. The investigation was conducted through a search of publications in the Web of Science database, using "stakeholder," "management," and "corporate governance" as keywords. This search resulted in 57 articles published between 1998 and 2024. Of these, 15 articles (published between 1998 and 2022) were selected for content analysis, based on the criterion of highest citation count. For the analysis of the textual content of the abstracts of the 57 articles found and the 15 selected articles, the IRAMUTEQ software (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires) was used. This free tool, based on the R software, allows for processing and statistical analysis of textual data. It is concluded that the convergence between stakeholder management, corporate social responsibility (CSR), and transparency has become an increasingly relevant area of study, reflecting the importance of ethics and sustainability as pillars of modern corporate governance.